The Effect of the Implementation of Moodle-Based E-Learning Media on Student Learning Outcomes - Asna Paputungan; Roy Hasiru; Fatmawaty Damiti; Melizubaida Mahmud; Abdulrahim Maruwae (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to determine the effect of Moodle-based e-learning on the social studies learning outcomes of grade IX students at MTs Negeri 3 South Bolaang Mongondow. The research employed a quantitative approach with a Quasi-Experimental design using the Posttest-Only Control Group Design. The sample consisted of 43 students from classes IX A and IX B. Data were collected through observation, tests, and documentation. The data were then analyzed using an Independent Sample T-test. The findings revealed that the average posttest score of the control class was 61.91, while the experimental class, which used Moodle-based e-learning, scored an average of 84.15. The significance value obtained was 0.000 (p < 0.05), indicating a statistically significant difference between the two groups. These results suggest that the use of Moodle-based e-learning has a positive impact on student learning outcomes in social studies. Therefore, it can be concluded that Moodle is more effective than conventional learning methods in enhancing students’ academic performance.